2016
DOI: 10.1073/pnas.1609417113
|View full text |Cite
|
Sign up to set email alerts
|

Minibrain and Wings apart control organ growth and tissue patterning through down-regulation of Capicua

Abstract: The transcriptional repressor Capicua (Cic) controls tissue patterning and restricts organ growth, and has been recently implicated in several cancers. Cic has emerged as a primary sensor of signaling downstream of the receptor tyrosine kinase (RTK)/extracellular signal-regulated kinase (ERK) pathway, but how Cic activity is regulated in different cellular contexts remains poorly understood. We found that the kinase Minibrain (Mnb, ortholog of mammalian DYRK1A), acting through the adaptor protein Wings apart (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 51 publications
3
47
0
Order By: Relevance
“…The C-terminal tail of human CSN1 also directly interacts with IκB . We likewise detected a physical interaction between CSN1b and Cic, consistent with a previous mass spectrometry study (Yang et al, 2016), suggesting that direct binding may underlie the effect of CSN1b on Cic stability. Interestingly, Drosophila has a second CSN1 subunit, CSN1a, which lacks the PCI domain and is primarily expressed in the testis (Flybase), and human CSN1 has multiple alternatively spliced isoforms and can be phosphorylated (Fang et al, 2008;Fuzesi-Levi et al, 2014).…”
Section: Deneddylase-independent Functions For Csn1bsupporting
confidence: 91%
See 1 more Smart Citation
“…The C-terminal tail of human CSN1 also directly interacts with IκB . We likewise detected a physical interaction between CSN1b and Cic, consistent with a previous mass spectrometry study (Yang et al, 2016), suggesting that direct binding may underlie the effect of CSN1b on Cic stability. Interestingly, Drosophila has a second CSN1 subunit, CSN1a, which lacks the PCI domain and is primarily expressed in the testis (Flybase), and human CSN1 has multiple alternatively spliced isoforms and can be phosphorylated (Fang et al, 2008;Fuzesi-Levi et al, 2014).…”
Section: Deneddylase-independent Functions For Csn1bsupporting
confidence: 91%
“…The other highly conserved and essential domains of Cic, the high-mobility group (HMG)-box DNA-binding domain and the C1 motif (Astigarraga et al, 2007), might influence its stability in unstimulated cells. The kinase Minibrain (Mnb) was recently found to phosphorylate Cic on its Nterminus, inhibiting its repressive activity (Yang et al, 2016). Mnb and its adaptor Wings apart do not affect Cic stability, but this finding hints that other mechanisms for Cic regulation may remain to be discovered.…”
Section: Regulation Of Capicua Degradationmentioning
confidence: 99%
“…a), and the C2 deletion mutant is insensitive for MAPK‐induced downregulation . The ERK‐independent downregulation of CIC by minibrain /DYRK1A is observed in Drosophila wing and eye formation . In addition, bicoid antagonizes downregulation of CIC in anterior patterning of Drosophila .…”
Section: Structure and Function Of Capicua/cicmentioning
confidence: 99%
“…(18,33) The ERK-independent downregulation of CIC by minibrain/DYRK1A is observed in Drosophila wing and eye formation. (34) In addition, bicoid antagonizes downregulation of CIC in anterior patterning of Drosophila. (35,36) In this case, bicoid acts as a competitive substrate for MAPK, which renders CIC phosphorylation.…”
mentioning
confidence: 99%
“…Cic was first identified in a screen for mutations affecting tissue patterning in Drosophila embryos . In Drosophila , several studies revealed that Cic regulates not only anteroposterior and dorsoventral body patterning but also intestinal stem cell proliferation, wing development, and other processes in development …”
mentioning
confidence: 99%